2013
DOI: 10.1089/scd.2012.0604
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Restores Amyloid Beta-Inhibited Proliferation of Neural Stem Cells by Activating the PI3K Pathway

Abstract: Neurogenesis in the adult brain is important for memory and learning, and the alterations in neural stem cells (NSCs) may be an important part of Alzheimer's disease pathogenesis. The phosphatidylinositol 3-kinase (PI3K) pathway has been suggested to play an important role in neuronal cell survival and is highly involved in adult neurogenesis. Recently, coenzyme Q10 (CoQ10) was found to affect the PI3K pathway. We investigated whether CoQ10 could restore amyloid β (Aβ)25-35 oligomer-inhibited proliferation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Based on our previous studies, the PI3K/AKT pathway is inhibited by Aβ and its recovery by diverse ways is helpful for the prevention of Aβ toxicity [14,15,54]. This finding is also supported by many other researchers [55][56][57].…”
Section: The Alteration Of the Pi3k/akt Pathway In Adsupporting
confidence: 65%
See 2 more Smart Citations
“…Based on our previous studies, the PI3K/AKT pathway is inhibited by Aβ and its recovery by diverse ways is helpful for the prevention of Aβ toxicity [14,15,54]. This finding is also supported by many other researchers [55][56][57].…”
Section: The Alteration Of the Pi3k/akt Pathway In Adsupporting
confidence: 65%
“…Therefore, GSK-3β inhibition through the activation of PI3K/AKT can be another solution for the treatment of AD. We have reported that GV1001, which is a novel vaccine peptide mimicking Human telomerase reverse transcriptase (hTERT), donepezil, and coenzyme Q10 can block Aβ through the activation of PI3K and AKT and then the inhibition of GSK-3β [14,54,67]. Although the Phase II clinical trial using NP031112, a GSK-3β inhibitor, has not yet shown definite efficacy to AD patients, it showed that its usage was safe.…”
Section: The Therapeutic Possibility Of the Modulation Of The Pi3k/akmentioning
confidence: 99%
See 1 more Smart Citation
“…The proliferation of neurocytes in these regions has been studied in various AD mouse models, but the findings have been inconsistent. Although an overall trend of impaired neurocyte proliferation in these areas in AD has been documented [32,33,34,35], Kamphuis et al . [36] and Díaz-Moreno et al [37] observed enhanced proliferation in APP/PS1 and SAMP8 mice, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, CoQ10 oral administration restores oxygen consumption levels in the brain of aged animals [74] and exerts antihyperglycemic effects [23-25]. In addition, previous reports have indicated the usefulness of CoQ10 supplementation on memory processing by improving hippocampal cholinergic function via increasing cholineacetyltransferase and decreasing acetylcholinesterase activities [53], neurogenesis via reducing amyloid-β formation [75, 76], reducing oxidative stress markers, and increasing ATP levels in hippocampus and cortex [53]. Therefore, the sum of CoQ10 supplementation on decline of hyperglycemia, oxidative stress, neuronal apoptosis, and improved cholinergic activity, vascular function, brain blood flow, and metabolism may contribute to the attenuation of DM-induced memory impairment in the present study.…”
Section: Discussionmentioning
confidence: 99%